MEDIATING EFFECT OF PROFITABILITY ON LEVERAGE AND INSTITUTIONAL OWNERSHIP INFLUENCING BANK DIVIDEND POLICY IN INDONESIA - Timotius Timotius; Indra Widjaja (Graduate Program of Universitas Tarumanagara, 2025)
The purpose of this study is to examine the effect of leverage and institutional ownership on dividend policy, with profitability as a mediating variable represented by Return on Equity (ROE) in banking sector listed on the Indonesia Stock Exchange between 2021 and 2024. This quantitative study makes use of secondary data in the form of financial statements gathered from the official websites of the Indonesia Stock Exchange and Banks. Data analysis is performed using a panel data regression model and Sobel test with EViews 9.0 software. The sample consists of 17 banks selected using purposive sampling based on specific criteria. The study's findings reveal that Leverage, as measured by debt-to-equity ratio (DER), does not significantly impact Return on Equity (ROE). In contrast, Institutional Ownership, as measured has a positive impact on ROE. Furthermore, the direct relationships between Institutional Ownership and ROE were found positive and significant. However, neither DER nor ROE show a significant direct impact on dividend policy measured by dividend payout ratio (DPR). Additionally, the analysis indicates that ROE does not mediate the relationship between leverage or institutional ownership and dividend policy.